Case Series Report on Clinico-Pathological and Radiological Correlation of Atypical Meningiomas - Dr. Bhavadasan k, Dr. Nilesh Potdar, Dr. S Suresh Kumar (International Journal of Innovative Research in Medical Science, 2017)
Aims and Objective: - 1- Study of neuroradiological finding of atypical meningiomas. 2- Correlation of intra operative finding and histopathological diagnosis and prognosis after surgery. Method: - Fourty eight cases of meningioma were treated surgically in our hospital between January 2014 and dec 2016. Eleven (22%) were histologically identified as aggressive variant of meningioma.Here study cases of aggressive variant of meningiomas operated , according to their neuroradiological finding and histopathogical and intra operative findings . Result:-We found 11 cases of meningiomas found to be of atypical variety and aggressive in nature. Six of them were recurrent meningiomas. Bony erosion were found in five cases, three cases having heterogeneous contrast enhancement, four cases having brain invasion. HPR result showing, three cases having malignant meningiomas and six cases having atypical meningioma. Conclusion:-CT and MRI gave useful information for the possible diagnosis of the atypical meningioma before surgery. Predicting histological nature meningioma would aid in surgical and treatment planning.